2000
DOI: 10.1074/jbc.275.20.15399
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Expression of Placental Lactogen in the Beta Cells of Transgenic Mice Results in Beta Cell Proliferation, Islet Mass Augmentation, and Hypoglycemia

Abstract: The factors that regulate pancreatic beta cell proliferation are not well defined. In order to explore the role of murine placental lactogen (PL)-I (mPL-I) in islet mass regulation in vivo, we developed transgenic mice in which mPL-I is targeted to the beta cell using the rat insulin II promoter. Rat insulin II-mPL-I mice displayed both fasting and postprandial hypoglycemia (71 and 105 mg/dl, respectively) as compared with normal mice (92 and 129 mg/dl; p < 0.00005 for both). Plasma insulin concentrations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
188
3
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(212 citation statements)
references
References 36 publications
20
188
3
1
Order By: Relevance
“…The ratio of plasma insulin to blood glucose was higher in the GDNF-tg mice compared to WT mice. This is similar to what was observed in transgenic mice that overexpress placental lactogen in β-cells that also have increased β-cell mass 20 . The capacity of GDNF to diminish chemically induced β-cell destruction was also demonstrated in vivo.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The ratio of plasma insulin to blood glucose was higher in the GDNF-tg mice compared to WT mice. This is similar to what was observed in transgenic mice that overexpress placental lactogen in β-cells that also have increased β-cell mass 20 . The capacity of GDNF to diminish chemically induced β-cell destruction was also demonstrated in vivo.…”
Section: Discussionsupporting
confidence: 87%
“…Our studies demonstrate a three-fold increase in β-cell mass in GDNF-tg mice compared to WT mice. This degree of enhancement is similar to the three-fold increase in β-cell mass observed in other growth factor overexpression studies, including PTH-RP and placental lactogen 20,21 . It is important to note that the effects of GDNF on β-cells is not a systemic effect as serum GDNF levels have been measured in GDNF-tg mice and are no different from littermate controls 10 .…”
Section: Discussionsupporting
confidence: 86%
“…However, exogenous addition of lactogenic peptides did not confer complete protection against GLT-mediated beta cell death. Previously, we found that lactogens can protect rodent beta cells against other cell death inducers including STZ and DEX [23][24][25][26]. Recent findings show that PRL also protects human beta cells against different cell death inducers, including cytokines, hydrogen peroxide and serum-starvation [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Mouse strains These studies used 3-6-month-old male and female RIP-mPl1 transgenic mice bred onto a CD-1 background [24,25], and 3-8-month-old male and female Bclxl lox/lox mice [30] kindly provided by L. Hennighausen (National Institutes of Health (NIH)/National Institute of Diabetes and Digestive and Kidney Diseases (NIDDK), Bethesda, MD, USA). All studies were performed with the approval of, and in accordance with, guidelines established by the University of Pittsburgh Institutional Animal Care and Use Committee, and principles of laboratory animal care were followed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation